Visualizing Fluorescence: Using a Homemade Fluorescence “Microscope” to View Latent Fingerprints on Paper - LaFratta, Christopher N. (2010)
We describe an inexpensive handheld fluorescence imager (low-magnification microscope), constructed from poly(vinyl chloride) pipe and other inexpensive components for use as a teaching tool to understand the principles of fluorescence detection. Optical filters are used to select the excitation and emission wavelengths and can be easily interchanged to accommodate different fluorescent samples. As a demonstration, we used the fluorescence imager to view lawsone-dyed fingerprints on paper, which fluoresce red when illuminated with green light. This emission can be seen by viewing the sample through the instrument by eye, or the fluorescence can be captured by a camera. The entire imager can be built for less than $300.